Legal Analysis of Criminal Regulations in Cases Criminal act Child Abuse Under Law Child Protection Act - Maekal Ananta Pratama Ginting; Hasdiana Juwita Bintang; Henry Aspan (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
In Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection, there is an article that prohibits obscene acts, which is regulated in Article 76E which reads: